MODELING SHARE PRICES OF BANKS AND BANKRUPTS - KITOV, Ivan O. (Theoretical and Practical Research in Economic Fields; Vol 1 No 1 (2010): TPREF, Volume I, Issue 1(1), Summer 2010, 2010)
Share prices of financial companies from the S&P 500 list have been modeled by a linear function of consumer price indices in the USA. The Johansen and Engle-Granger tests for cointegration both demonstrated the presence of an equilibrium long-term relation between observed and predicted time series. Econometrically, the pricing concept is valid. For several companies, share prices are defined only by CPI readings in the past.  Therefore, our empirical pricing model is a deterministic one. For a few companies, including Lehman Brothers, AIG, Freddie Mac and Fannie Mae, negative share prices could be foreseen in May-September 2008. One might interpret the negative share prices as a sign of approaching bankruptcies.